2021
DOI: 10.1136/bmjopen-2020-042735
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of continuous monitoring of vital signs in surgical patients on a general ward: an observational cohort study

Abstract: ObjectiveTo determine feasibility, in terms of acceptability and system fidelity, of continuous vital signs monitoring in abdominal surgery patients on a general ward.DesignObservational cohort study.SettingTertiary teaching hospital.ParticipantsPostoperative abdominal surgical patients (n=30) and nurses (n=23).InterventionsPatients were continuously monitored with the SensiumVitals wearable device until discharge in addition to usual care, which is intermittent Modified Early Warning Score measurements. Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…3AHcare, which has been researched and developed, integrates physiological parameters such as ECG, respiration, blood oxygen, blood pressure, and temperature into the same sensor chip. SD card is used to store data, and Zigbee or Bluetooth technology is used to transmit data to intelligent terminals for display, so as to realize daily monitoring of patients with chronic diseases in family and community environment [ 9 ]. Wireless ECG monitoring system based on body area network can collect patients' ECG data in real time and transmit them to mobile phone mobile terminals, and the system can analyze and mine the data to assist medical staff in monitoring patients' physiological information [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…3AHcare, which has been researched and developed, integrates physiological parameters such as ECG, respiration, blood oxygen, blood pressure, and temperature into the same sensor chip. SD card is used to store data, and Zigbee or Bluetooth technology is used to transmit data to intelligent terminals for display, so as to realize daily monitoring of patients with chronic diseases in family and community environment [ 9 ]. Wireless ECG monitoring system based on body area network can collect patients' ECG data in real time and transmit them to mobile phone mobile terminals, and the system can analyze and mine the data to assist medical staff in monitoring patients' physiological information [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our protocol seeks to specify the frequency of artefacts using both automatic detection with predefined bounds but also with review by clinicians as reported in a study concerning the feasibility of continuous monitoring of vital signs in surgical patients on a general ward using SensiumVitals patch. 21 This study showed a high percentage of artefacts concerning the respiratory rate measurement (51% of the measurements), and a lower percentage concerning the heart rate measurement (19%) and temperature (9%). This point is crucial as artefacts will generate false alarms leading to the rejection of the technique by caregivers.…”
Section: Discussionmentioning
confidence: 54%
“…There are some studies that use the surgical patient as a research population. However, these are usually studies which take place in-hospital or in which the patient has been in the hospital for several days between surgery and discharge [27][28][29][30]. Therefore, Some limitations need to be addressed as well.…”
Section: Discussionmentioning
confidence: 99%